2015
DOI: 10.1038/aps.2014.153
|View full text |Cite
|
Sign up to set email alerts
|

Orally administered moxifloxacin prolongs QTc in healthy Chinese volunteers: a randomized, single-blind, crossover study

Abstract: Aim: To investigate the QT/QTc effects of orally administered moxifloxacin in healthy Chinese volunteers. Methods: This was a single-blinded, randomized, single-dose, placebo-controlled, two-period cross-over study. A total of 24 healthy Chinese volunteers were enrolled, randomly assigned to two groups: one group received moxifloxacin (400 mg, po) followed by placebo with a 7-d interval, another group received placebo followed by moxifloxacin with a 7-d interval. On the days of dosing, 12-lead 24 h Holter ECGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…drugs if not well tolerated or suggested to include in case of isoniazid resistance (3)(4)(5). In general, the toxicity profile of moxifloxacin is rather mild, though it includes concentration-dependent corrected QT interval prolongation and, rarely, tendinopathy (6)(7)(8)(9). A clinically relevant drug-drug interaction is the combination of moxifloxacin with rifampin, since these two drugs can be used concomitantly in TB treatment.…”
mentioning
confidence: 99%
“…drugs if not well tolerated or suggested to include in case of isoniazid resistance (3)(4)(5). In general, the toxicity profile of moxifloxacin is rather mild, though it includes concentration-dependent corrected QT interval prolongation and, rarely, tendinopathy (6)(7)(8)(9). A clinically relevant drug-drug interaction is the combination of moxifloxacin with rifampin, since these two drugs can be used concomitantly in TB treatment.…”
mentioning
confidence: 99%
“…Similar trends in the heart rate and PR interval were observed in the halothane-anaesthetized dogs, which did not achieve statistical significance [7]. Meanwhile, the negative chronotropic and dromotropic effects have not been reported in human beings [12]. The cardiohemodynamic results indicate that moxifloxacin-induced histamine release might not occur in microminipigs, whereas these electrophysiological ones suggest that microminipigs may be more sensitive animals for detecting the negative chronotropic and dromotropic effects of moxifloxacin than dogs.…”
Section: Pharmacokineticmentioning
confidence: 81%
“…In this study, we used microminipigs to investigate the pharmacokinetic and cardiovascular profiles of moxifloxacin and terfenadine, which are known to induce ‘benign’ and ‘malignant’ QT interval prolongation, respectively . A fluoroquinolone antibiotic moxifloxacin is known to induce mild QT interval prolongation and has been recommended as a positive control by regulatory authorities to evaluate the sensitivity and reliability of QT/QTc studies because of its absence of clinical data on the onset of torsade de pointes . Meanwhile, an antihistamine, terfenadine, has been withdrawn from the market in 1997 because of its high risk of QT interval prolongation followed by the onset of torsade de pointes .…”
mentioning
confidence: 99%
“…These plasma levels correspond to approximately 5–15% inhibition of hERG by cisapride in pure serum and are in the range of the calculated IC 10 value which measured 182 nM. For moxifloxacin, the total plasma levels of 20–24 μM prolonged QTc by 30–31 ms (Johannesen et al ., ) whereas two other studies showed a 2.0–2.5 ms increase in QTc for every 1000 ng ml −1 (2.5 μM) moxifloxacin yielding calculated QTc increases of 8–10 and 24–30 ms for the total plasma levels of 10 and 30 μM, respectively (Chen et al ., ; Morganroth et al ., ). These concentrations (10–30 μM) produce 3.5–9.4% inhibition of hERG channel current by moxifloxacin in serum and are close to the IC 10 value of 32 μM.…”
Section: Discussionmentioning
confidence: 99%